2020
DOI: 10.3390/ma13051105
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Property Investigation of Mold Inhibitor Treated Raw Cotton and Ramie Fabric

Abstract: At present, research rarely focuses on side effects of the use of mold inhibitors on raw cotton and ramie fabric. Four different mold inhibitors (dimethyl fumarate (DMF), ethyl p-hydroxybenzoate (EHB), propyl p-hydroxybenzoate (PHB), and calcium sorbate (CS)) were used to treat raw cotton and ramie fabric through a dipping method. The optical properties, wettability, thermal conductivity, thermal stability, and combustion properties of treated cotton and ramie samples have been investigated. The reflectance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Pineapple leaf fibre (PALF) is a naturally occurring fibre that is obtained from the leaves of the pineapple plant [29]. The structure of PALF is identified by its ribbon-like shape, which is composed of a vascular bundle system.…”
Section: Plant Fibre's Physical and Mechanical Propertiesmentioning
confidence: 99%
“…Pineapple leaf fibre (PALF) is a naturally occurring fibre that is obtained from the leaves of the pineapple plant [29]. The structure of PALF is identified by its ribbon-like shape, which is composed of a vascular bundle system.…”
Section: Plant Fibre's Physical and Mechanical Propertiesmentioning
confidence: 99%
“…In China, the annual output of RF accounts for more than 95% of the world [12]. Compared with other plant fibers, the RF has excellent moisture absorption, air permeability and microbial erosion resistance, and its length and strength are much higher than cotton fiber [13,14]. The crystallinity of RF is also higher than that of cotton fiber [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For wider application, mechanical properties of green composites using natural fibre have been studied [7]- [12]. In addition, fibre products using woven and knit fabrics using natural fibres have been studied to assess their compatibility with sustainable development goals (SDGs) [13]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [20] reported aspects of the thermal stability of cotton fabric. Thermogravimetric analyses revealed that thermal degradation of pure cotton occurred at 298°C.…”
Section: Introductionmentioning
confidence: 99%